Smart library utilization strategy to enhance teachers' reading interest in elementary schools - Indrayani, Indrayani; Hidayati, Dian (Universitas Ahmad Dahlan, 2023)
Reading is a crucial tool for unlocking the gateway to knowledge and plays a vital role in personal development. Engaging in reading allows individuals to refine comprehension skills from various angles, preventing engagement in risky behaviors due to a lack of knowledge. In educational settings, students look to their teachers for guidance and inspiration, including setting an example through reading books. Despite quality libraries and literacy programs, student interest in reading may not reach its full potential if teachers fail to act as reading role models. Unfortunately, enthusiasm for reading among teachers in Indonesia remains low. This research aims to uncover the availability of reading media in elementary schools utilizing the e-Library application (Smart Library). It focuses on the design of a reading media utilization program and the strategic implementation to enhance teachers' reading interest. Additionally, the research evaluates the impact of this media and program on teachers. A descriptive qualitative approach is employed, with research subjects from elementary schools in Bandung using Smart Library. Data collection techniques include observation, interviews, and documentation. Findings reveal the Smart Library Utilization Strategy Model to Increase Teachers' Reading Interest in Elementary Schools, comprising four steps: (1) Schools should provide comfortable reading media meeting teachers' needs, digital and physical; (2) School principals must design an innovative and diverse reading media utilization program to effectively enhance teachers' reading interest; (3) Implementation should proceed through strategic steps, from socialization to appreciation; and (4) Regular evaluation of teachers' reading interest improvement is essential to assess quality and identify factors influencing it.